Unemployment and social exclusion: a longitudinal study - Galić, Zvonimir; Šverko, Branimir (2007)
The social exclusion theory posits a downward spiral, in which unemployment leads to poverty and social isolation, which in turn reduce the chances for re-employment. However, the evidence for this process is mainly cross-sectional. In this paper we seek to verify the implied relations longitudinally. The purpose was to examine whether and how the prolonged unemployment affects the other two components of social exclusion, i.e., economic deprivation and social isolation. The data came from a survey carried out in Croatia in 2003 (T1), repeated in 2004 (T2), and again in 2005 (T3). Four groups of participants, all unemployed at T1, were compared (N=385): participants who remained unemployed at T2 and T3 ; participants who were employed at T2 and T3 ; participants who were unemployed at T2 and employed at T3 ; and participants who were employed at T2 and unemployed at T3. Their household income and expressions of financial concerns were used to assess their economic deprivation. Social isolation was measured by one 4-point item concerning feelings of being an integral part the social community. The analysis of data revealed pronounced differences among the groups. The individuals who remained unemployed during the observed period experienced further aggravation of their financial hardship and increase in social isolation, while those who got a job exhibited improvement. The results of the group that gained and lost the job were in accordance: loosing a job was associated with pronounced increase of economic deprivation and social isolation. The results clearly confirm that that prolonged unemployment not only impoverishes, but also socially isolates affected people. The implications of the findings for the social exclusion theory are discussed.
Projekt MZOS
ENG